Reassessing the Turkish Model in the Post-Cold War Era: A Role Theory Perspective - ERŞEN, EMRE; PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2014)
This article aims to discuss and analyze the emergence and evolution of Turkey's role as a model in the international system in three different periods, 1991-93, 2003-05 and 2010-12. To this end, it methodologically uses the main concepts of role theory: role expectations, role conceptions and role performance. Focusing on K.J. Holsti's example national role conception category in particular, it seeks to reveal the major similarities and differences between the role expectations that have enacted the role conception known as the Turkish model, and compare the impact of these expectations on role performance in each of these three cases. The major argument of the article is that the sustainability of the model's national role conception depends foremost on Turkey's political and economic capabilities that directly influence its role performance.
Keywords: NATIONAL ROLE CONCEPTIONS; FOREIGN-POLICY; EURASIA; VISION; LIMITS; BASES